Stakeholder’s Preference and Rational Compliance: A Comment on Sacconi’s “CSR as a Model for Extended Corporate Governance II: Compliance, Reputation and Reciprocity” - Francés-Gómez, Pedro (Journal of business ethics, 2008)
Lorenzo Sacconi’s recent re-statement of his social contract account of business ethics is a major contribution to our understanding of the normative nature of CSR as the expression of a fair multi-party agreement supported by the economic rationality of each participant. However, at one crucial point in his theory, Sacconi introduces the concept of stakeholders’ conformist preferences – their disposition to punish the firm if it defects from the agreement, refusing to abide by its own explicit CSR policies and norms. We take issue with him over this concept: we show that the assumption of conformist preferences is a moral premise, and it arguably weakens the normativity of the theory as a whole. As an alternative, we propose an evolutionary game theoretic approach. We draw upon recent applications of evolutionary game theory to moral philosophy (Skyrms, Danielson), and we use a computer simulation of the trust game. According to this approach, the failure of the logic of reputation, which is the problem conformist preferences were introduced to solve, is overcome through the dynamics of interaction.